FEMINISM AS DEPICTED IN THE POETRY OF SITANATH ACHARYA - Pati, Nibedita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sita Nath Acharya, a veteran Sanskritist of Bengal, is a poet of post-modern Sanskrit poetry. Several post-modern themes like feminism, gerontology, nationalism, terrorism, crimes and antisocial behaviors etc. have been reflected in his poetry. The present paper incorporates an analysis on post-modern theme like feminism which is described in the poetry of Sita Nath Acharya.